Limited Irrigation for Sweet Corn Planted at Different Dates on Claypan Soil. Issue 1 (11th August 2016) - Sweeney, Daniel W.; Kirkham, M.B.; Marr, Charles W.
Abstract : Irrigation sources in the claypan soil areas of the eastern Great Plains are limited, but supplemental irrigation at certain growth stages may help lessen crop stress. The objective of this research was to determine the effect of critically timed, limited‐amount irrigation on yield and growth of sweet corn ( Zea mays L.) planted at two dates with different levels of N fertilization. During the three years of this study, planting date influenced both the total number and total fresh weight of harvested sweet corn, but the effect of early and late plantings was not consistent. Early plantings resulted in up to 65% more harvested ears, nearly twice the total fresh weight yields, and increased number of ears/plant and individual ear weight, especially when plantings were delayed in one year because of inclement weather conditions. But early plantings also can result in lower production when rainfall is great and temperatures are cool. Although irrigation at the V12 and R1 growth stages was found to improve sweet corn yield by as much as 30% over no irrigation, especially when planted late, droughty conditions were not prevalent at the site used in this study and the benefit was sporadic with few differences between irrigation timings. On this site, N fertilization rates had little effect on sweet corn production. Growth of sweet corn was mainly affected by planting date, but dry matter produced during the season was not a consistent indicator of yield.